Element‐Specific Magnetization Damping in Ferrimagnetic DyCo5 Alloys Revealed by Ultrafast X‐ray Measurements. Issue 8 (13th August 2021) - Abrudan, Radu; Hennecke, Martin; Radu, Florin; Kachel, Torsten; Holldack, Karsten; Mitzner, Rolf; Donges, Andreas; Khmelevskyi, Sergii; Deák, András; Szunyogh, László; Nowak, Ulrich; Eisebitt, Stefan; et al.
Abstract : In article number 2100047, Ilie Radu and co‐workers provide experimental and theoretical evidence for an element‐specific magnetic damping parameter by investigating the ultrafast magnetization response of ferrimagnetic DyCo alloys to femtosecond laser excitation. These novel insights are of utmost importance for understanding the physics of non‐equilibrium magnetism as well as for modeling laser‐driven magnetic recording phenomena and ultrafast spintronics.